Combination of antiplatelet and anticoagulant therapy, component network meta-analysis of randomized controlled trials - Szapáry, László; Tornyos, Dániel; Kupó, Péter; Lukács, Réka; El Alaoui El Abdallaoui, Oumaima; Komócsi, András (Frontiers in Cardiovascular Medicine, 2022)
Background Despite numerous randomized clinical trials (RCT), data regarding the efficacy of antiplatelet and anticoagulant combinations are still conflicting. We aimed to analyze treatment options tested in various fields of cardiovascular prevention, regarding their efficacy and bleeding risk. Methods Systematic searches of electronic databases were conducted until June 2022. A component network meta-analysis was performed in R. Risk estimates across trials were pooled using random-effects model selecting risk ratio (RR) with 95% confidence intervals (95% CIs) as summary statistics. The primary endpoint of interest was the rate of major cardiac adverse events (MACE). Major bleeding events were assessed as main safety endpoint. Secondary outcomes included cardiovascular- and overall mortality, myocardial infarction (MI), stent thrombosis, and stroke. Results Fifteen studies randomizing 73,536 patients were identified. The MACE risk reflected heterogeneity among the anticoagulants with dabigatran and apixaban significantly reducing the risk of MACE (RR 0.56; 95% CI 0.39–0.80 and RR 0.75; 95% CI 0.58–0.98, respectively). Vitamin K antagonist (VKA), rivaroxaban, or edoxaban did not reduced of MACE while it was associated with a significant increase of bleeding risk (RR 1.66; 3.66, and 5.47, respectively). The direct anticoagulant (DOAC) dose reduction resulted in tendencies of fewer bleeding but higher MACE risk, while combination with aspirin was followed with increased risk for bleeding, however, remained non-significant in these cases. Conclusion Our meta-analysis supports that the ischemic-bleeding balance is different among direct-acting oral anticoagulants (DOACs) while this is not significantly affected by the dose reduction approaches. Long-term aspirin treatment as part of the anticoagulant and dual antiplatelet regimen provides no ischemic benefit but may increase bleeding risk. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [259703].